Optimal scheduling of an EV aggregator for demand response considering triple level benefits of three-parties - Ren, Hui; Zhang, Aiwei; Wang, Fei; Yan, Xihui; Li, Yu; Duić, Neven; Shafie-khah, Miadreza; Catalão, João P.S. (Elsevier, 2021)
The electric vehicle (EV), when aggregated by an agent (Aggregator), is a suitable candidate for participating in demand response in power system operation. As the interface between distribution network and EV users, as well as an independent party at the same time, an optimal scheduling algorithm is necessary with consideration of benefits of three parties, which in return will affect aggregators’ sustainable development. The benefits of distribution system from demand response, aggregator and EV users are defined in this paper. EV users’ benefit is described by their satisfaction on SOCs reached after a given period of time and overall costs/revenues for charging/discharging and policy award/penalty, while the benefit of distribution network for the integration of large amount EV loads through aggregator is evaluated by aggregator’s load shifting capability through a price-based demand response (DR) program under real time electricity price. The optimal scheduling of the aggregator is with an objective of maximizing its own benefit under constraints of EV users’ minimum satisfaction and minimum load-shifting capability required by distribution network. The optimization scheduling is tested by a test system, and further analysis is given on the effect of aggregator’s facility level and technology (Vehicle to Vehicle) and the operation mode of aggregator group on the benefits of three parties.
Keywords: aggregator; demand response; electric vehicle; Load shifting; Users’ satisfaction; Vehicle to Vehicle; electric vehicles; fi=Sähkötekniikka|en=Electrical Engineering|